(untitled) (Fiep Bulletin - online, 2014)
The evolution human being for an erect position provided for the man a gamma of functional benefits, however, the style of modern life also caused it morphologic alterations of the structure muscle-skeletal as problems in the position and patologias of the vertebral column. Objectives: To analyze the prevalence of scoliosis in schoolboys of the municipal public net of education of the city of João Pessoa/PB. The study is characterized how study of cases, descriptive, transversal of qualitative boarding of the type. One evaluated 73 schoolboys with ages between 07 and 10 years old of the city of João Pessoa/PB. Each student had the prickly processes of the vertebral column marked after flexão of the trunk, being then photographed the coasts in static position, identifying the type of escoliose and registering it. The sample presented average of age of 8,63±1,16 years and the prevalences of escolioses were of 62,9%, being these cervical 6.8%, 31.5% torácica, lumbar 19.1%, 2.8% cervical-thoracic. It was concluded that scoliosis was considerably prevalent between the pertaining to school searched, having itself to explore the reasons related to this type of pathology, since the trend is the aggravation of this.